Adding metformin to the oral contraceptive treatment for hirsutism has no additional effect on Ferriman-Gallwey scores in hirsute women with PCOS: A randomized controlled study - (:unkn) unknown (My University, 2004)
0

OBJECTIVE: To analyze the additional benefits of adding metformin to the oral contraceptive pill (OCP) treatment in lean women with PCOS. STUDY DESIGN: After a baseline work-up including BMI, waist-to-hip ratio, Ferriman-Gallwey (FG) score, serum hormone, SHBG, fasting glucose and insulin levels, 28 nonobese women with PCOS were randomized either to the OCP or to the OCP-plus-metformin treatment. At the end of the 4-month follow-up period, subjects were re-evaluated. RESULTS: The two groups were similar at baseline. The effects of the two treatments on the FG score were similar. Subjects, who received OCP-plus-metformin had significantly higher reductions in serum androstenedione than those, who received OCP alone. Fasting glucose-to-insulin ratio improved significantly in the OCP-plus-metformin group, while OCP treatment alone did not cause any significant change. CONCLUSIONS: Adding metformin to the OCP treatment may result in additional benefits, but does not improve hirsutism over the OCP treatment alone.
Keywords: Kadın Hastalıkları ve Doğum